PSYCHOLINGUISTIC MECHANISMS OF TERMINOLOGY ACQUISITION AND THEIR ROLE IN ORAL FLUENCY DEVELOPMENT - Khasanova Shakhnoza Zokhirovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This paper examines theoretical perspectives on terminology acquisition, explores the cognitive and neuropsychological processes involved, and analyzes how psycholinguistic insights inform teaching strategies for oral competence. Emphasis is placed on task-based practice, retrieval-enhancing techniques, multimodal input, and scaffolding strategies that facilitate automaticity, fluency, and pragmatic accuracy in professional contexts.